2008
DOI: 10.1111/j.1365-2230.2007.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the eotaxin gene −426C→T, −384A→G and 67G→A single-nucleotide polymorphisms and atopic dermatitis in Italian children using family-based association methods

Abstract: Our results suggest that in our group of children with AD, the eotaxin gene may play a crucial role in the development of extrinsic AD, probably with other genetic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
7
2
Order By: Relevance
“…Batra et al 15 found both a significant relationship between eotaxin‐1 +67 G>A genotype and asthma and a correlation between mutant genotype and plasma eotaxin level. However, other studies did not support these findings 7,16 , 18 . The present study failed to show an association between eotaxin‐1 +67 G>A genotypes and NP.…”
Section: Discussioncontrasting
confidence: 95%
“…Batra et al 15 found both a significant relationship between eotaxin‐1 +67 G>A genotype and asthma and a correlation between mutant genotype and plasma eotaxin level. However, other studies did not support these findings 7,16 , 18 . The present study failed to show an association between eotaxin‐1 +67 G>A genotypes and NP.…”
Section: Discussioncontrasting
confidence: 95%
“…Given the report that SNP rs111568837 in the promoter of CCL11 correlated with the incidence of atopic dermatitis in an Italian cohort [ 15 ], we investigated whether rs111568837 also was associated with FM. However, the transmission of this SNP from parents to probands was not statistically significant ( S2 Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study [ 12 ], we showed that several inflammatory chemokines were elevated in FM, including CCL11 and CCL4, genes located in a chemokine gene cluster on chromosome 17. This chemokine locus is associated with atopic dermatitis [ 15 ] and IBD [ 16 ], both immune-related disorders. As a follow-up to the GWAS FM family study on chromosome 17 [ 6 ], we performed functional studies on the chemokine gene-cluster region on chromosome 17 by exome sequence and functional analyses.…”
Section: Introductionmentioning
confidence: 99%
“…68 A second cluster including chemokine genes (CCL5, CCL16, CCL14, CCL15, CCL23, CCL18, CCL3 and CCL4) located further upstream has also been studied in relation to MS, but in this study we have focused on the centromeric cluster, as this was identified in the rat linkage study. Through meta-analysis of several MS cohorts from Nordic countries we could collect a large number of MS patients and controls from a relatively homogenous population and thereby identify association to haplotypes in CCL2 and CCL13, and a single marker in CCL1.…”
Section: Discussionmentioning
confidence: 99%